Distribution in a high-level economy - Cox, Reavis; Goodman, Charles S.; Fichandler, Thomas C. (Englewood Cliffs, N.J. : Prentice-Hall, 1965)
This book considers two of the most persistent questions raised about the American system of distribution; how large a part does distribution play in a highly developed economy? how effective does it perform the functions allotted to it in the American way of life?.
Bibliographical footnotes.
gp. 23/01/2019
Loan
Keywords: Marketing